Interview 5 - Abubakari, Yushawu
This file contains the interview notes with Naambia. Naambia (Pseudonymized) is 24 years and the second born of his family. He has been in the business for 4 years. Naambia completed secondary school and has not been able to continue his education. Naambia occupies a middle position in the scamming industry. He has people he works under and those who work under him too. The interview was done in Getto where he always spend his free time with his friends